2012
DOI: 10.1016/j.eats.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Proximal Hamstring Repair and Ischial Bursectomy

Abstract: Abstract:With the significant increase in use of the arthroscope around the hip have come several less invasive techniques to manage pathologies around this joint. This technical note with a video details one such technique that allows for the endoscopic management of proximal hamstring tears and chronic ischial bursitis, which until now have been managed exclusively with much larger open approaches. This procedure allows for complete exposure of the posterior aspect of the hip in a safe, minimally invasive fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 26 publications
0
57
0
Order By: Relevance
“…19 The risk of infection and other complications related to extensive open approaches has recently led to the successful development of full-endoscopic techniques for addressing hamstring origin tears. 8,13,14 Thus far, there have been no studies reporting the results or complications of full-endoscopic techniques. As shown at meetings and in technical notes, the hamstring origin repair can be achieved by experienced surgeons trained in hip arthroscopy and extraarticular endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The risk of infection and other complications related to extensive open approaches has recently led to the successful development of full-endoscopic techniques for addressing hamstring origin tears. 8,13,14 Thus far, there have been no studies reporting the results or complications of full-endoscopic techniques. As shown at meetings and in technical notes, the hamstring origin repair can be achieved by experienced surgeons trained in hip arthroscopy and extraarticular endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, treatment of hamstring origin avulsions is still controversial, and surgery has been recommended in the literature for osseous avulsions with more than 2 cm of retraction, complete avulsions in all 3 tendons with or without retraction, and partial avulsions that remain symptomatic despite nonoperative treatment. 5,6,8 Although good results have been reported with open surgery, [9][10][11][12] Dierckman and Guanche, 13 as well as other authors, 8,14 have been successfully leading the implementation of new endoscopic techniques to avoid complications due to extensive open approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For open repairs, a variety of surgical incisions have been described including transverse incisions within the gluteal fold, longitudinal incisions extending distally from the gluteal fold, and Tshaped incisions utilizing components of both these incisions. More recently, endoscopic techniques to address proximal hamstring pathology have been described, [93][94][95] although the ideal indications and candidates for endoscopic techniques continue to evolve.…”
Section: Primary Surgical Repairmentioning
confidence: 99%
“…In 2012, Dierckman and Guanche72 described a technique for endoscopic repair of partial proximal hamstring avulsions. They found that this resulted in smaller incisions than a traditional open technique, as well as protection of the sciatic nerve by complete visualisation during the repair.…”
Section: Introductionmentioning
confidence: 99%